Four new sequestrate species of Russulaceae found in China - Sang, Xiaoyu; Li, Xuedong; Wang, Yanwei; Fan, Li (Phytotaxa, 2016)
Four new sequestrate species of Russulaceae are described and illustrated from China in this study. Accepting the concept that both the agaricoid and sequestrate species were actually derived from the same origin, we placed these hypogeous taxa in Russula or Lactarius as Lactarius spinosporus, Russula absphaerocellaris, R. brevipileocystidiata and R. megapseudocystidiata. Morphologically, L. spinosporus differs L. falcatus by its brown gleba, the lack of latex and the thick-walled terminal elements in the peridiopellis; R. absphaerocellaris differs from Gymonomyces gilkeyae by the small basidiospores ornamented with short spines; R. brevipileocystidiata is distinguished from Cystangium clavatum by the absence of hymenial cystidia and a stipe-columella; R. megapseudocystidiata is different from Cystangium bisporum by the grooved basidiomata and the abundant laticiferous hyphae in the peridial context. Both ITS and nrLSU sequence-based phylogenetic analyses revealed that the four sequestrate species were nested in the Russula or Lactarius clade, but respectively in their own clusters, also supporting these novel taxa as distinct species.